Splitting out of Class: Family and Social Class as Schizophrenogenic Forces in Frank McGuinness’s Observe the Sons of Ulster Marching Towards the Somme - Merve Hançer (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
McGuinness’s The Sons of Ulster Marching Towards the Somme (1985) can be considered an exemplary play in which he asserts how historical, political, and social institutions impact individuals, resulting in schizoid states. This study of family and social class as oppressive institutions in Irish society, as reflected in Sons of Ulster, examines the split self of the main character, Kenneth Pyper with respect to Deleuze and Guattari’s1 schizoanalysis theory, which considers the idea of split self into social and self-identity as emancipation from social and political pressures. Pyper’s split self will be interpreted from a cultural–critical standpoint rather than a “clinical schizophrenic” one. In this way, McGuinness criticizes family and social class institutions as schizophrenogenic forces that constrain the individual by splitting the main character into Elder and Younger Pyper in Sons of Ulster.